Short‐term outcomes of multicenter prospective cohort study of gastric endoscopic resection: 'Real‐world evidence' in Japan. Issue 1 (25th September 2018) - Suzuki, Haruhisa; Takizawa, Kohei; Hirasawa, Toshiaki; Takeuchi, Yoji; Ishido, Kenji; Hoteya, Shu; Yano, Tomonori; Tanaka, Shinji; Endo, Masaki; Nakagawa, Masahiro; Toyonaga, Takashi; Doyama, Hisashi; et al.
Abstract : Objectives: A Japanese multicenter prospective cohort study examining endoscopic resection (ER) for early gastric cancer (EGC) has been conducted using a Web registry developed to determine the short‐term and long‐term outcomes based on absolute and expanded indications. We hereby present the short‐term outcomes of this study. Methods: All consecutive patients with EGC or suspected EGC undergoing ER at 41 participating institutions between July 2010 and June 2012 were enrolled and prospectively registered into the Web registry. The baseline characteristics were entered before ER, and the short‐term outcomes were collected at 6 months following ER. Results: Nine thousand six hundred and sixteen patients with 10 821 lesions underwent ER (endoscopic submucosal dissection [ESD]: 99.4%). The median procedure time was 76 min, and R0 resections were achieved for 91.6% of the lesions. Postoperative bleeding and intraoperative perforation occurred in 4.4% and 2.3% of the patients, respectively. Significant independent factors correlated with a longer procedure time (120 min or longer) were as follows: tumor size >20 mm, upper‐third location, middle‐third location, local recurrent lesion, ulcer findings, gastric tube, male gender, and submucosa. Histopathologically, 10 031 lesions were identified as common‐type gastric cancers. The median tumor size was 15 mm. Noncurative resections were diagnosed for 18.3% of the lesions. Additional surgery was performed for 48.6% (824 lesions) of the 1695 noncurative ER lesions with a possible risk of lymph node (LN) metastasis. Among them, 64 (7.8%) exhibited LN metastasis. Conclusions: This multicenter prospective study showed favorable short‐term outcomes for gastric ESD.